The Birth of Muhammadiyah in Sukabumi: Cikal Bakal Lahirnya Muhammadiyah di Sukabumi - Saleh, Munandi; Noor, Iqbal; Sulaeman, Sulaeman (Civilization Research: Journal of Islamic Studies, 2024)
The purpose of this research is to find out the origin of Muhammadiyah in Sukabumi. This research uses a historical approach by using descriptive analysis and interview methods and is complemented by library research using books and other related literature. Based on the research results, he is the Muhammadiyah organization which was originally a social organization founded by a Middle Eastern modernist alumnus K.H. Ahmad Dahlan (Muhammad Darwis) on November 18 1912 in Yogjakarta. The forerunner of this organization only appeared in Sukabumi around 1935 at the same time as the arrival of martial arts figures from Garut to Sukabumi, while its official establishment began in 1950 at the same time as the Islamic People's School (SRI) was founded on Jl. R. Syamsudin 53 which is an extension of the Islamic People's School (SRI) from Cipetir. This organization was founded by K.H. Dahlan and his student Abdullah Mansyur as well as two community leaders in Sukabumi City, namely Emo Harja and Kurdi.